A biological origin for gravel mounds in inland Australia. Issue 5 (4th July 2018) - Schmidt, L.
ABSTRACT: More than 1000 near-circular mounds up to 40 m diameter and 2.1 m high, which contain 15–1250 m 3 (mean 159 m 3 ) of gravel, have been identified in western New South Wales. Mounds are more pebble-rich than the surrounding surface regolith and contain abundant pebbles to 1196 g weight. Resemblance to smaller gravel nest mounds of the malleefowl ( Leipoa ocellata ) suggests they were constructed by a similar although larger bird. Pebbles were inadvertently concentrated in the nest mounds during construction and maintenance. Formation by geological mechanisms, as burrow spoil or burial mounds is not compatible with the features of the mounds. The mounds are undated, but partial blanketing by eolian sand suggests they predate the Last Glacial Maximum. The mounds are now spatially associated with Casuarina trees. Pollen records in southeastern Australia reveal that shrub and grassland replaced Casuarina woodland as aridity increased after ca 35 000 yrs BP. Climate change driven habitat loss in the semi-arid zone likely caused the extinction of the apparently Casuarina woodland dependent megapode responsible for the gravel mounds. The mounds partly map the megapode distribution and provide an opportunity to date the local extinction of a megafauna member, compare this to climate and vegetation changes, and determine the duration of overlap with human occupation.